Entrepreneurial Leadership in Cultivating an Organizational Culture of Innovation for Sustainable and Circular Agriculture Strategies in Farmer Groups - Sugiarto, Dadet; Riyadi, Selamet; Mudjijah, Slamet; Susanto, Jemmy; Faiqoh, Dina Nadiyah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine entrepreneurial leadership in fostering an organizational innovation culture for sustainable and circular agricultural strategies among farmer groups. This study employs a mixed-methods approach to explore the relationships between entrepreneurial leadership, organizational culture, and the adoption of sustainable agricultural practices. Quantitative data from structured surveys and qualitative insights from interviews and focus group discussions highlight how entrepreneurial leadership significantly correlates with the implementation of sustainable agricultural techniques such as composting, integrated pest management, and resource-saving practices. Research findings reveal that entrepreneurial-minded leaders not only inspire behavioral change but also create systems for continuous learning and exchange of ideas among farmers. These leaders empower farmers to adapt solutions to local conditions, strengthen collaboration among farmers, and connect with external networks to obtain knowledge and resources. The study emphasizes that fostering an innovation-oriented culture within agricultural communities is crucial for achieving climate resilience, food security, and ecological sustainability. This research highlights the strategic importance of leadership development, participatory approaches, and supportive ecosystems in enabling a farmer-led transition towards sustainable and circular agriculture